Hebrew popular journalism - Elyada, Ouzi.
1 online resource.
Keywords: The book examines the birth, development, and mode of operation of the Hebrew popular press that progressed in Ottoman Palestine between 1884 and the eruption of World War I in 1914. The inquiry yields a profile of the printers, editors, and journalists, and examines the editors' working patterns, the gathering of journalistic information, and distribution of the resulting product in the public sphere. Addressing the fact that nearly all of the Hebrew press in the eighteenth and nineteenth centuries appealed to an elitist intellectual and affluent readership, the book breaks new ground by showing that from the 1880s onward, a popular press came into being in Palestine for the first time in the history of the Hebrew press. The focus is on three popular newspapers that evolved in Jerusalem along the lines of the Western popular press. While profiling the readership of the popular Hebrew press the book also investigates reading practices. Analysing the contribution of the press to the modernization of the Hebrew language, this pioneering volume is a key resource for students and scholars of communication, media and Hebrew studies, and media and Jewish history.